Connecting climate science and society: reflections from early and mid-career researchers at the World Climate Research Programme Open Science Conference 2023 - Díaz, Leandro B.; Gulizia, Carla; Jain, Shipra; Langendijk, Gaby S.; Palanisamy, Hindumathi; Rabanal, Valentina; Charlton, Candice S.; Dajuma, Alima; Donkor, Felix K.; Egbebiyi, Temitope S.; Kondi Akara, Ghafi; Jrrar, Amna; et al. (Frontiers in Climate, 2025)
This paper reflects the discussions of early and mid-career researchers (EMCRs) during the World Climate Research Programme Open Science Conference 2023 EMCRs Symposium, to advance climate knowledge for greater transformative power in society and impact on policy-making. These discussions focused on three key priority challenges: how to produce robust, usable, and used climate information at the local scale; how to address key climate research and knowledge gaps in the Global South; and how EMCRs could support policy-making with climate information. We present here our perspective on these major challenges, possible ways to address them, and what could be the contribution of EMCRs. In addition, we provide recommendations for actions that could be taken at the international and national levels to increase the voice and leadership of Global South researchers and EMCRs in international scientific endeavors. These recommendations might facilitate the integration of new technological tools or innovative approaches, promote interdisciplinary collaboration, and foster connections with local communities. This coordinated approach to international, regional and local initiatives will catalyze the process for urgent action on the environmental crisis before us.